2016
DOI: 10.4103/2278-0203.192114
|View full text |Cite
|
Sign up to set email alerts
|

Fluoride influences nickel-titanium orthodontic wires′ surface texture and friction resistance

Abstract: Objectives:The aim of this study was to investigate the effects exerted by the acidulated fluoride gel on stainless steel and nickel-titanium (Ni-Ti) orthodontic wires.Materials and Methods:Sixty stainless steel and Ni-Ti orthodontic archwires were distributed into forty archwires used for in vitro study and twenty for in situ study. Fluoride was applied for 1 h in the in vitro experiment while it was applied for 5 min in the in situ experiment. The friction resistance of all wires with ceramic brackets before… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 29 publications
4
19
0
Order By: Relevance
“…It was shown that the in vitro fluoride application caused an increase in friction resistance of Ni-Ti wires when compared to stainless steel wires. In vitro and in situ fluoride application caused deterioration in surface properties of Ni-Ti wires 54 . Some studies have investigated the differences between various types of brackets in terms of adhesion of cariogenic streptococci.…”
Section: Discussionmentioning
confidence: 99%
“…It was shown that the in vitro fluoride application caused an increase in friction resistance of Ni-Ti wires when compared to stainless steel wires. In vitro and in situ fluoride application caused deterioration in surface properties of Ni-Ti wires 54 . Some studies have investigated the differences between various types of brackets in terms of adhesion of cariogenic streptococci.…”
Section: Discussionmentioning
confidence: 99%
“…[21] Our observations also agree with the result of in-situ studies on the effects of fluoride and intraoral environment on TMA and Ni-Ti wires done by Abbassy et al ., which has reported the coverage of TMA wires with corrosion products and peeling of surface with numerous deep grooves following fluoride use intraorally, and the effects were same with Ni-Ti wires. [1422] These studies did not give a quantitative assessment as they had used SEM for evaluating the surface property. Reports from another in-vitro study conducted on commercially pure titanium using neutral fluoride solutions show that fluoride concentration more than 0.1% produced severe corrosion.…”
Section: Discussionmentioning
confidence: 99%
“…[10] With the added usage of neutral fluoride mouthwashes, the corrosion of these wires increases. [2223] According to Abbassy, the protective titanium oxide film on the surface of the wire undergoes a reaction in fluoride solutions resulting in the formation of titanium fluoride, titanium oxide fluoride, or sodium titanium fluoride on the surface of the alloy. Corrosion resistance decreases markedly and destruction of oxide layer leads to the absorption of hydrogen from various solutions because of the high affinity of titanium to hydrogen called “hydrogen embrittlement.”[23] After immersion of TMA in fluoride solution, the fracture mode is also said to change from ductile to brittle with a decrease in tensile strength.…”
Section: Discussionmentioning
confidence: 99%
“…At present, many orthodontists use sliding mechanics for the closure of extraction spaces. During sliding mechanics, biological tissue response and tooth movement only happen when the applied force overpowers the friction between brackets and archwires [10,11]. Evidence shows that about 50% of the load required for tooth movement is spent to overcome the friction force [12].…”
Section: Introductionmentioning
confidence: 99%
“…According to a study by Walker et al [18] in 2007, the concentration of fluoride can serve as an important factor in the failure of the protective oxide layer of alloys; this superficial oxide layer, which is eliminated by fluoride, prevents oxygen diffusion and confers corrosion resistance to SS and titanium molybdenum alloy (TMA) wires [18]. Many studies have evaluated the effect of fluoride mouthwash on surface properties of wires and brackets, particularly surface roughness and friction in fixed orthodontic systems [1,11,12,18,19].…”
Section: Introductionmentioning
confidence: 99%